Evaluation of the Effectiveness of Composite Mineral Remediation Agents on Cd Immobilization in Soils and Rice. Issue 3 (3rd April 2022) - Zhang, Junji; Shi, Zeming; Liu, Shuting; Ni, Shijun; Wang, Xinyu; Huang, Weiwen
ABSTRACT: Accumulating heavy metal contamination in soils caused by industrial waste, fertilizer, and wastewater irrigation is a matter of grave concern for the environment and food safety. In recent years, remediation agents with the characteristics of economy, high efficiency, and simple operation have become a popular choice for remediation of heavy metal contaminated soil. By far, there are relatively few studies evaluating the effects on remediation agents for their both heavy metal passivation and soil fertility promotion. This study investigated the effects of a remediation agent on Cd passivation, soil pH, and heavy metal uptake by rice crops. Eight treatments were used to evaluate the effect of Cd immobilization in soil. Changes in soil pH and soil Cd fractions were monitored during incubation for 30 days. The field study was conducted during the whole growth stages of rice crops, samples of rice plants and soil at the tillering, booting, and harvesting stages were collected and tested. Cd fractions were extracted from soil at different stages to investigate the effects of various treatments on Cd uptake and bioaccumulation in rice plants. The results show that composite mineral remediation agents composed of mineral fertilizer and synthetic zeolite could effectively improve the pH of soil in incubation experiments and field experiments. Composite mineral remediation agents were effective in stabilizing Cd and increasing rice yield. Mineral fertilizer and Synthetic zeolite played an important role in the tillering stage and harvesting stage of rice growth in field, respectively. Group A4 (mineral fertilizer: synthetic zeolite at mass ration of 10:6) had the best results. Compared with control experiment (CK), HOAc extractable Cd of A4 group decreased by 6%, oxidizable Cd of A4 group increased by 2%, and the residue Cd of A4 group increased by 4%.